Dynamics of Charge Transients in High Voltage Silicon and SiC NPN BJT Under High Injection Levels - Mana Hosseinzadehlish; Saeed Jahdi; Konstantinos Floros; Ingo Ludtke; Xibo Yuan (IEEE Open Journal of Power Electronics)
This article evaluates the dynamic performance of high voltage Silicon and 4H-SiC NPN BJTs based on experimental measurements together with modeling through Silvaco TCAD to describe the charge transient dynamics. The measurements are performed with a DC-link voltage of 800 V at peak collector current of 14 A. A range of base currents modulated by base resistors are employed with two load inductors to enable a wide range of switching conditions at different switching rates. The TCAD model is validated by comparing with datasheet while double-pulse switching events have delivered the experimental switching transients. In the Silicon BJT case, the device is shown to exhibit very significant turn-off delays compared to 4H-SiC BJTs, particularly under high-level injection conditions. The absence of delay in 4H-SiC BJTs is due to the lower minority carrier lifetime and thinner base region, enabling higher DC gain and significantly faster transients. However, the current drop phenomenon is clearly seen in the 4H-SiC BJT in both measurements and TCAD modelling, which unlike the Silicon, is very sensitive to the peak collector current at HLI for a fixed base current due to its thinner base and more susceptance to the Early effect. The Silicon BJT does not exhibit such trend, given its wide base region, though its inability to eliminate the depletion regions at on-state with HLI is demonstrated by rise of voltage while still conducting, as demonstrated by TCAD and measurements.